The flexible programming of thermodynamic cycles: Application of supercritical carbon dioxide Brayton cycles. (1st October 2021) - Zhao, Dongpeng; Deng, Shuai; Zhao, Ruikai; Zhao, Li; Xu, Weicong; Long, Xiting
Graphical abstract: Highlights: A method that integrates parametric and graphical analysis of cycles is proposed. Three basic logical operations in the flexible programming of cycles are identified. A complex cycle can be decomposed into several simple cycles using this method. Parametric analyses of complex cycles only need physical models of simple cycles. The method provides a new perspective to easily understand complex cycles. Abstract: A growing number of complex thermodynamic cycles, such as different configurations of supercritical carbon dioxide (sCO2 ) Brayton cycles, have been recently proposed. However, the understanding and analysis of complex cycles are very arduous and time-consuming, due to the lack of a general theory for cycle analysis and numerous equations included in physical models of cycles. To address these challenges, a novel method named the flexible programming of thermodynamic cycles (FPTC) is developed based on the graphical analysis in the T-s diagram. Within the theoretical framework of the FPTC, the complex cycle can be obtained by performing logical operations of several simple cycles in the T-s diagram. Meanwhile, the type of logical operation also determines the relationship of the thermodynamic performance indexes (heat input, heat output, net-work output, and thermal efficiency) between the synthetic complex cycle and simple cycles. There are three basic types of logical operation (addition, subtraction, and interchange) in the FPTC, and the detailed rules in each logical operation are presented by using the Carnot cycle as the basic simple cycle. In the case study, four different configurations of sCO2 Brayton cycles are analyzed using the FPTC, and their evolutions from simple Brayton cycles to complex are shown. Meanwhile, the thermal efficiencies of different configurations can be calculated by efficiency formulas obtained from the FPTC. Results show this case analysis is an efficient approach to analyze complex cycles. The FPTC is not only a graphical analysis method to study the evolution of complex cycles, but also provides a simple method to calculate the performance of synthetic complex cycles. It allows researchers to evaluate the performance of synthetic cycles by physical models of simple cycles, instead of building physical models for complex cycles. Furthermore, the FPTC also provides a new perspective for constructing or designing complex thermodynamic cycles.